Robust and adaptive model predictive control of non-linear systems - Guay, Martin, 1966-; Adetola, Veronica; DeHaan, Darryl (IET control, robotics and sensors series, 2015)
The following topics are dealt with: adaptive control; constrained nonlinear systems; disturbance attenuation; robust adaptive economic MPC; and discrete-time systems.